Energy Literacy Among Secondary School Students: A Multidimensional Study of Sociodemographic Patterns and Energy-Use Behavior - Mira Pitriyani; Muhammad Syukri; Evendi Evendi; Abdul Halim; Irwandi Irwandi; Siti Maghfirah; Nurazidawati Mohamad Arsad (Jurnal Pendidikan Progresif, 2026)
This study addresses the need for evidence-based energy education that links conceptual understanding to students’ daily energy behaviors. This study analyzes the energy literacy of secondary school students across the domains of knowledge, attitudes, and behavior, examining the effects of age, gender, grade level, parental education, and participation in advanced physics electives. The study employed a quantitative survey using an energy literacy questionnaire adapted from the Energy Literacy Questionnaire framework. After data cleaning and reversing scores on negative statements, 303 valid responses were analyzed using descriptive statistics, Cronbach’s alpha reliability test, Kruskal-Wallis test, epsilon squared effect size, and Bonferroni post-hoc test. Students’ total energy literacy fell into the moderate category (M = 68.80). The knowledge (M = 72.32), attitude (M = 67.70), and behavior (M = 66.37) domains were also in the moderate category, with behavior being the lowest domain. Gender significantly differentiated knowledge and total literacy, while grade level significantly differentiated the knowledge domain. Age,  father’s education, mother’s education, and enrollment in Physics as an elective subject did not significantly differentiate total literacy. Students’ energy literacy is multidimensional and reveals a knowledge-action gap. Energy education needs to shift from conceptual learning toward real-world projects, school-based practices, and family engagement. Keywords: energy literacy, adolescent students, gender, socioeconomic status, parental education.